2008
DOI: 10.1242/dev.021097
|View full text |Cite
|
Sign up to set email alerts
|

Cited2 is required for the proper formation of the hyaloid vasculature and for lens morphogenesis

Abstract: *Cited2 is a transcriptional modulator with pivotal roles in different biological processes. Cited2-deficient mouse embryos manifested two major defects in the developing eye. An abnormal corneal-lenticular stalk was characteristic of Cited2 -/-developing eyes, a feature reminiscent of Peters' anomaly, which can be rescued by increased Pax6 gene dosage in Cited2 -/-embryonic eyes. In addition, the hyaloid vascular system showed hyaloid hypercellularity consisting of aberrant vasculature, which might be correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 62 publications
(102 reference statements)
3
41
0
Order By: Relevance
“…This might be due to unidentified function(s) mediated by Shroom3 that are distinct from those involving p120-catenin. Several mouse mutants that display a similar lens stalk phenotype have disruptions in additional morphogenetic processes, such as proliferation, adhesion, differentiation and apoptosis, leaving open the possibility that Shroom3 might also function in these processes (Dimanlig et al, 2001;Ozeki et al, 2001;Medina-Martinez et al, 2005;Yoshimoto et al, 2005;Chen et al, 2008;Pontoriero et al, 2008Pontoriero et al, , 2009Kuracha et al, 2011;Cavalheiro et al, 2014).…”
Section: P120-catenin and Shroom3 Are Required For Normal Lens Morphomentioning
confidence: 99%
“…This might be due to unidentified function(s) mediated by Shroom3 that are distinct from those involving p120-catenin. Several mouse mutants that display a similar lens stalk phenotype have disruptions in additional morphogenetic processes, such as proliferation, adhesion, differentiation and apoptosis, leaving open the possibility that Shroom3 might also function in these processes (Dimanlig et al, 2001;Ozeki et al, 2001;Medina-Martinez et al, 2005;Yoshimoto et al, 2005;Chen et al, 2008;Pontoriero et al, 2008Pontoriero et al, , 2009Kuracha et al, 2011;Cavalheiro et al, 2014).…”
Section: P120-catenin and Shroom3 Are Required For Normal Lens Morphomentioning
confidence: 99%
“…[2][3][4][5][6] In particular, Cited2 plays an important role in fetal liver hematopoiesis, which is supported by severely impaired fetal liver HSC function and decreased expression of genes known to be essential for hematopoiesis in Cited2-deficient fetal liver HSC/progenitors. 7 Cited2 has also been implicated in tumor cell invasion and progression.…”
Section: Introductionmentioning
confidence: 99%
“…11 In our previous studies, we showed that deletion of HIF-1␣ partially rescues defects in heart and lens caused by Cited2 deficiency. 4,12 In addition, at the structural level, Freedman et al revealed that Cited2 and HIF-1␣ share a conserved "LPXL" sequence motif in their transactivation domains that interacts directly with a binding site on the CH1 region of CBP/p300. 13 HIFs are recognized as master modulators of the cellular response to hypoxic stress.…”
Section: Introductionmentioning
confidence: 99%
“…Knockout of Cited2 is embryonic lethal, and the embryos display multiple developmental defects, including heart, lung, liver, and eyes (17)(18)(19)(21)(22)(23)(24). Mechanistically, HIF-1, TFAP2, and Nodal-Pitx2 pathways are in part responsible for heart defects in Cited2 Ϫ/Ϫ mice (17,19,20,25).…”
mentioning
confidence: 99%